Altered GPM6A/M6 Dosage Impairs Cognition and Causes Phenotypes Responsive to Cholesterol in Human and Drosophila. Issue 12 (December 2014) - Gregor, Anne; Kramer, Jamie M.; van der Voet, Monique; Schanze, Ina; Uebe, Steffen; Donders, Rogier; Reis, André; Schenck, Annette; Zweier, Christiane
<x xml:space="preserve">Abstract</x> We found a de novo duplication of GPM6A in a patient with learning disability and behavioral problems. Altered dosage of human GPM6A in patient lymphoblastoid cells caused an increased presence of cells carrying membrane protrusions, while tissue specific dosage manipulation of the fly counterpart M6 resulted in wing defects, lethality and impaired memory in Drosophila. We could improve some of these by supplementation of cholesterol. Our findings further emphasize a role of cholesterol in cognitive function and dysfunction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>